DEVELOPMENT OF STARTER SYSTEM DIRECT DRIVE TYPE SIMULATOR AS LEARNING MEDIA IN AUTOMOTIVE ELECTRICAL SYSTEM COURSES - Kusyandi, Kusyandi; Mubarak, Ibnu (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
This research discuss about the development of android based learning media which aims to develop, assess and knowing student responses of the Simulator Pemeriksaan dan Pengujian Sistem (SEMESTA). Learning activity that is usually carried out directly in laboratory can not be held due to Covid-19 Pandemic. Therefore, learning media is needed by utilizing digital platforms that are able to provide virtual practical experiences. The use of Android smartphones is an alternative in developing virtual learning media. This learning media was developed using the Research and Development (RD) method with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The learning media developed was assessed by experts (expert judgement) and students. The results showed that the assessment of three media experts got an average score of 4.6 with a proportion of 92.5% and three material experts of 4.7 with a percentage of 93% which could be categorized as very proper because the media was built with considering learning media feasibiliies criteria. While the results of the student’s responses were obtained by 85.7% which could be categorized as very good because this learning media was developed in digital platform which student’s interested to, attractive, and easy to operate. Based on the results, it can be concluded that SEMESTA learning media is very proper to be used for Automotive Electrical System courses.